Analysis Of Giving Reward By The Teacher To Motivate Students in Learning English at The Second Grade of SMK Cendana Padang Panjang - Hayatul Husna; Syahrul, Syahrul (Indonesian Research Journal on Education, 2023)
In teaching English as a foreign language for students, teacher must have the ability to provide positive reinforcement. One way that can be done by the teacher is to give rewards to students. At SMK Cendana Padang Panjang, the researcher found that: contrast to other subject teachers, the English teacher gave a rewards in every meeting. Even though the students answered the questions incorrectly, the teacher still gave rewards to them. In addition, the teacher also never differentiate students in the class, it means that rewards are not only given to the smartest students in the class, but also be given to those who answerquestions or do assignments correctly. The researcher used descriptive qualitative research design. The type of the research was an analysis. The purpose of the research was to describe about giving rewards by teachers to motivate students in learning English in class XI SMK Cendana Padang Panjang. The informant of this research was the English teacher of class XI at SMK Cendana Padang Panjang. Furthermore, the supporting informants was students of class XI TKJ 2 SMK Cendana Padang Panjang. In order to collect the data, the researcher used observation and interview. Based on the finding, givingrewards by the teacher can increase students' motivation in learning English. There were two types of rewards used by the teacher, namely verbal and non-verbal. At the time of learning, teacher more often used rewards in the form of verbal. The teacher’s reasons gave rewards to students were to appreciate every effort that has been made by students and to arouse students' motivation in learning English.